2016
DOI: 10.1007/s00292-016-0176-6
|View full text |Cite
|
Sign up to set email alerts
|

Grading der Tumoren des hepatobiliären Systems

Abstract: Tumors of the liver, intrahepatic and extrahepatic bile ducts as well as the gallbladder are very heterogeneous and show different biological behavior. The 4‑stage (i.e. well, moderately, poorly and undifferentiated) grading system for hepatocellular carcinoma proposed by the WHO takes tumor size and architecture as well as the extent of cell and nuclear pleomorphism into account. In addition, the WHO defines some special forms of hepatocellular carcinoma. For carcinomas of intrahepatic bile ducts the WHO prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Adenoma is also a type of neoplastic polyp of the GB and is usually classified into tubular, papillary, and mixed types. 5 Epidemiological data have shown that tubular adenomas are less common with a lower risk of malignant transformation than papillary adenomas, and papillary adenomas are considered a premalignant condition of the GB.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoma is also a type of neoplastic polyp of the GB and is usually classified into tubular, papillary, and mixed types. 5 Epidemiological data have shown that tubular adenomas are less common with a lower risk of malignant transformation than papillary adenomas, and papillary adenomas are considered a premalignant condition of the GB.…”
Section: Discussionmentioning
confidence: 99%